2005
DOI: 10.1177/009102600503400104
|View full text |Cite
|
Sign up to set email alerts
|

Human Resource Management in American Counties, 2002

Abstract: Human resource management (HRM) in public organizations is changing as there are numerous policy, procedural and structural reforms underway. Human resource management studies have focused primarily at the state and federal levels, with relatively fewer comprehensive views of county governments. This article looks at human resource management roles, structures and practices from the perspective of county government using data from the Government Performance Project. The article describes approaches to reforms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…Under NPM, this traditional approach came to be seen as something of a liability, undermining performance and demotivating individuals (Farnham and Horton 1996; Bach and della Rocca 2000). In a move mirrored by governments around the developed world (Selden 2005), what were perceived as ‘best practice’ concepts of people management, derived from the private sector, were held up as ideals to which the public sector should aspire (Kessler et al 2000; Bach and della Rocca 2000; Morgan and Allington 2002; Horton 2003; Harris 2004). Some of the core components of this imported model were: (1) performance‐based rewards for staff; (2) reducing the costs of employment; (3) empowering organizations to take strategic decisions in the HRM field; (4) increased flexibility in order to respond to customer demands; (5) increased individualization of the employment relationship; and (6) decentralization (Horton 2003; Farnham et al 2003; Skalen 2004).…”
Section: The Role Of Human Resource Management In the Public Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…Under NPM, this traditional approach came to be seen as something of a liability, undermining performance and demotivating individuals (Farnham and Horton 1996; Bach and della Rocca 2000). In a move mirrored by governments around the developed world (Selden 2005), what were perceived as ‘best practice’ concepts of people management, derived from the private sector, were held up as ideals to which the public sector should aspire (Kessler et al 2000; Bach and della Rocca 2000; Morgan and Allington 2002; Horton 2003; Harris 2004). Some of the core components of this imported model were: (1) performance‐based rewards for staff; (2) reducing the costs of employment; (3) empowering organizations to take strategic decisions in the HRM field; (4) increased flexibility in order to respond to customer demands; (5) increased individualization of the employment relationship; and (6) decentralization (Horton 2003; Farnham et al 2003; Skalen 2004).…”
Section: The Role Of Human Resource Management In the Public Sectormentioning
confidence: 99%
“…The consensus within the prescriptive literature is that a move towards a more strategic role is desirable, if not essential, to the future of the HR function (Ulrich and Beatty 2001; Jamrog and Overholt 2004), while the conclusion within the empirical literature is that the role enacted by HR functions in most organizations in fact remains primarily administrative or reactive (Truss et al 2002; Caldwell 2003; Lawler and Mohrman 2003; Guest and King 2004; Wright et al 2004; Selden 2005).…”
Section: The Role Of Human Resource Management In the Public Sectormentioning
confidence: 99%
“…For example, narrow and rigid classification plans, slow hiring processes, and procedural constraints limit investments in testing and training (Gresham & Andrulis, 2002;Selden, 2005). For example, narrow and rigid classification plans, slow hiring processes, and procedural constraints limit investments in testing and training (Gresham & Andrulis, 2002;Selden, 2005).…”
Section: Wfp As Strategic Adaptationmentioning
confidence: 99%
“…The consensus within the prescriptive literature is that a move towards a more strategic role is desirable, if not essential, to the future of the HR function (Jamrog and Overholt, 2004;Ulrich and Beatty, 2001), whilst the conclusion within the empirical literature is that the role enacted by HR functions in most organisations in fact remains primarily administrative or reactive (Selden, 2005;Guest and King, 2004;Wright et al, 2004;Caldwell, 2003;Lawler and Mohrman, 2003;Truss et al, 2002). …”
mentioning
confidence: 99%
“…Whilst some studies suggest that public sector HR functions have not adopted a more strategic role (Teo and Crawford, 2005;Selden, 2005;Harris, 2004;Jaconelli and Sheffield, 2000;Boyne et al, 1999;Barnett et al, 1996), there is some counter-evidence that HR functions are adopting a more strategic role; for instance, Kelly and Gennard (1996) found that some NHS HR directors were involved in strategising, and Stock et al (1994) found evidence of a move towards the increasing professionalisation of the HR role.…”
mentioning
confidence: 99%